Symmetry-breaking degrees of freedom in molecular perovskites - Boström, H (2018)
Perovskite oxides are functionally and structurally very diverse materials largely due to their abundance of symmetry-lowering degrees of freedom. A related and more nascent area of research is molecular perovskites: systems where at least one of the constituent ions is a polyatomic species. As a result of the topological congruence, molecular perovskites can often be understood in terms of the concepts developed for their inorganic congeners; yet the presence of polyatomic components imparts a higher level of ﬂexibility. This Thesis addresses the structural chemistry of molecular perovskites with regards to the effects of introducing molecular moieties. A special emphasis is placed on the existence and ramiﬁcations of “unconventional degrees of freedom”—deformations unrealisable in conventional perovskites. Three main themes are developed. First, the presence of polyatomic linking anions means that the BX6 octahedra are no longer corner sharing. Consequently, translational rigid unit phonon modes emerge, where columns or planes of octahedra displace relative to each other. These vibrations are referred to as “columnar shifts” and often constitute soft modes. Hence, they are prone to condensation upon cool- ing and can drive displacive phase transitions—like tilts in conventional perovskites. Second, as molecular linkers enhance the separation of the neighbouring metal units, the energy scale for B-site correlation is reduced. This is apparent in the coop- erative Jahn-Teller distortions in Cu-based systems, e.g. [C(NH2)3]Cu(HCOO)3, CuPt(CN)6 and Cu3[Co(CN)6]2. Dilution of the Cu2+ cations by Mn2+ generates orbitally disordered states at seemingly lower dilution levels than in solid solutions of inorganic perovskites. Third, it is demonstrated how the unconventional degrees of freedom expand the library of symmetry-breaking distortions. A key result is that molecular perovskites exhibit a comparatively high propensity for the adoption of acentric space groups via hybrid improper mechanisms; an impossible occurrence in conventional perovskites in the absence of layered order.